SQL-on-Hadoop: Full Circle Back to Shared-Nothing Database Architectures - Floratou, Avrilia; Minhas, Umar Farooq; Ozcan, Fatma (PVLDB, 2014)
SQL query processing for analytics over Hadoop data has recently gained significant traction. Among many systems providing some SQL support over Hadoop, Hive is the first native Hadoop system that uses an underlying framework such as MapReduce or Tez to process SQL-like statements. Impala, on the other hand, represents the new emerging class of SQL-on-Hadoop systems that exploit a shared-nothing parallel database architecture over Hadoop. Both systems optimize their data ingestion via columnar storage, and promote different file formats: ORC and Parquet. In this paper, we compare the performance of these two systems by conducting a set of cluster experiments using a TPC-H like benchmark and two TPC-DS inspired workloads. We also closely study the I/O efficiency of their columnar formats using a set of micro-benchmarks. Our results show that Impala is 3.3X to 4.4X faster than Hive on MapReduce and 2.1X to 2.8X than Hive on Tez for the overall TPC-H experiments. Impala is also 8.2X to 10X faster than Hive on MapReduce and about 4.3X faster than Hive on Tez for the TPC-DS inspired experiments. Through detailed analysis of experimental results, we identify the reasons for this performance gap and examine the strengths and limitations of each system.